Vulnerability and resiliency implications of human capital and linked inequality presence denial perspectives: Acknowledging Zigler's contributions to child well-being. (May 2021) - Nichols Lodato, Bronwyn; Hall, Jennifer; Spencer, Margaret Beale
Abstract: Edward Zigler's groundbreaking research on child development resulted in the historic Head Start program. It is useful to examine the theoretical implications of his work by applying a human development theoretical perspective. Phenomenological variant of ecological systems theory (PVEST) is a strengths-based theoretical framework that engages the variability of resource access and coping strategies that promote positive identity development for diverse children. While skill acquisition is a key focus of human capital theory's engagement of early childhood needs, this article highlights the on-going status of human vulnerability that undergirds identity development over the life course. The authors note that "inequality presence denial" combines with high-risk contexts, framed by geography and psychohistoric moments (e.g., The Great Recession, COVID-19), to alter diverse children's developmental pathways. The acknowledgement of "morbid risk" motivates the urgency for research that builds upon Zigler's innovations and privileges human development imperatives. The case study explores these concepts by examining the challenges and assets available to mothers in a low-income community. The article's closing notes developments in the field of economics that ameliorate human capital theory's conceptual limitations, underscoring human development's theoretical strength in motivating research and policies that are maximally responsive to children's positive identity development.